Taxonomic diversity of Ochrotrichiinae (Trichoptera: Hydroptilidae) from Peru with the description of ten new species, a new distributional record, and an updated checklist - Rocha, Isabela Cristina; Santos, Allan Paulo Moreira; Nessimian, Jorge Luiz (Zootaxa, 2023)
We describe here ten new species of Ochrotrichiinae from southern Peru in genera Metrichia (7 new species), Ochrotrichia (1 new species), and Rhyacopsyche (2 new species). In addition to describing and illustrating male genitalia of the new species, we also highlight diagnostic features from antennae, head setal warts, and wing venation. These structures have received little attention in taxonomic studies of Hydroptilidae, and we think they may be useful in future morphological studies involving the family. We also record O. puyana for the first time from Peru, which was previously known only from Ecuador. Comments on the distribution of the Peruvian Ochrotrichiinae are also provided, along with a distributional map and an updated checklist of the species recorded in the country. This work revealed a total of 56 species of Ochrotrichiinae from Peru.